Effectiveness of Antihypertension of Rennin Angiotension Inhibitor on Diabetic Patient with Hypertension - Leorita, Mesi; IDP, Pramantara; AE, Nugroho (International Journal of Science, Engineering, and Sustainable Technology (IJSESTech), 2014)
The combination of diabetes mellitus of type 2 and hypertension will increase risk of microvascular and macrovascular complications. Blood pressure which is controlled suitable to the targeted therapy may reduce the risk. American Diabetes Association (2013) recommended antihypertension of renin-angiotensin inhibitor, namely ACE inhibitor and angiotensin II receptor blockers, in order to control blood pressure of the patient of diabetes mellitus of type 2 and hypertension. The purpose of this study is to determine the effectiveness of the antihypertension of the renin-angiotensin system through two parameters, namely a) the percentage of therapeutic target attainment according to the JNC 8; and b) the value of blood pressure reduction. The study carried out by using a method of retrospective cohort study. The data were collected from the medical records of patient suffering both diabetes and hypertension at the Internal Disease Clinic of PKU Muhammadiyah Hospital, Yogyakarta. Descriptive analysis was conducted to determine the general characteristics of the patients. Bivariant analysis was carried out to determine three aspects, those are: 1) the profile of each of the antihypertension used (i.e., ACE inhibitors and angiotensin II receptor blockers) in inhibiting the renin angiotensin system, 2) the achievement (in %) of blood pressure treatment targets according to JNC 8, and 3) the value of blood pressure reduction. From 108 patients involved in this study, we obtained 117 patients who used antihypertension, consisting of 65 patients who used ACE Inhibitors and 52 patients who utilized angiotensin II receptor blocker. The average value of blood pressure reduction from the users of the ACE inhibitor is 20.55 ± 16.57 mmHg, while from the users of angiotensin II receptor blocker is 20.42 ± 15.41. We obtained that statistically the effectiveness of the two antihypertension groups of the renin-angiotensin inhibitors was the same.